(untitled) (Global Journal of Human-Social Science, 1970)
This study delves into the responses of women amidst the dynamic shifts within the ecumenical movement from 1910 to 1948 Two pivotal developments marked the burgeoning presence of women in missions during the early 20th century The Edinburgh World Missionary Conference of 1910 emerged as a cornerstone event within the ecumenical movement attracting numerous women missionaries representing diverse missionary societies and church mission boards Concurrently the Woman s Missionary Jubilee 1910- 11 underscored the fostering of camaraderie among women across First World and Third World churches These events catalyzed the integration of women into the fabric of Protestant missions leading to the formation of women s communities and their significant contributions to church establishment development and expansion However the establishment of the World Council of Churches WCC in 1948 ushered in a period of diminished opportunities for women s participation The predominant presence of male policy makers within the WCC particularly within the influential Central Committee which steered the Council between assemblies reflected a systemic gender disparity This shift prompted women to devise strategic approaches to bolster their roles within both church and society Consequently this paper aims to delineate the strategic initiatives undertaken by pioneering women leaders of the early 20th century to enhance the status of women leaders within the ecclesiastical and societal domains